Manajemen Persampahan di Kota Bukittinggi - Mulyani, Siti Rizka; Yoserizal, Yoserizal -; Putera, Roni Ekha (Sawala : Jurnal Administrasi Negara, 2018)
The environmental office of the City of Bukittinggi as the main mover in responsible waste management and encourages the community to be involved in solid waste management, that the waste problem will not be solved if only relying on the government, needs community support and participation, one of them is by establishing a waste bank. This study aims to describe how waste management is carried out by the City Government of Bukittinggi. The method used in this study is descriptive qualitative, data collection techniques using interviews, observation and documentation. To test the validity of the data found in the field with source triangulation techniques. The researcher used management theory by John F. Mee. Based on the results of the study, it can be concluded that the waste management carried out by the City Government of Bukittinggi has been going well. This can be seen from the application of a management perspective that plays an important role in the overall process of waste management starting from planning, organizing, giving motivation and supervision. But in the waste management process by the City Government of Bukittinggi there are still some problems and shortcomings in the management process, namely in the planning and organizing process.